Regularization techniques for inhomogeneous (spatial) point processes intensity and conditional intensity estimation****** - Coeurjolly Jean-Francois; Ba Ismaïla; Choiruddin Achmad (ESAIM: Proceedings and Surveys)
Point processes are stochastic models generating interacting points or events in time and/or space. Among characteristics of these models, first-order intensity and conditional intensity functions are often considered. We focus on inhomogeneous parametric forms of these functions assumed to depend on a certain number of spatial covariates. When this number of covariates is large, we are faced with a high-dimensional problem. This paper provides an overview of these questions and existing solutions based on regularizations.